Students’ Problem-solving Skills and Perceptions through Problem-based Learning Assisted by Google Classroom - Wulansari, Nur Iva; Putri, Febi; Yuliati, Lia; Nasikhudin, Nasikhudin (Tarbawi : Jurnal Ilmu Pendidikan, 2025)
Problem-solving skills are crucial for students to have in learning Newton's laws. However, it has been found that students are still relatively unsatisfied with these skills, which are still relatively unsatisfactory, so learning innovations that support and train these problem-solving skills are needed. In addition to training, students' perceptions of learning must be considered. This study aims to enhance problem-solving skills through the PBL model, assisted by Google Classroom (PBL-GC), on Newton's law material, and to investigate student perceptions of learning using a mixed-methods approach. The mixed-methods design used is an explanatory sequential design. Quantitative data were collected with a one-group pretest and posttest design and then analyzed with descriptive and inferential statistics. Then, qualitative data were collected to see students' thoughts about problem-solving skills and their perceptions of PBL-GC. The instruments used were problem-solving tests and semi-structured interview guidelines. The results indicate that PBL-GC has proven to improve problem-solving skills with an effect size of 1.62 in the strong category, and students have positive perceptions of their learning. The implications of the findings of this study strengthen theory and previous research and support educators in using the PBL model with different tools.